Masa Depan Kewirausahaan dan Inovasi: Tantangan dan Dinamika dalam Era Digital - Muhamad Zaenal Asikin; Muhamad Opan Fadilah (Jurnal Syntax Admiration, 2024)
This research aims to explore and analyze the challenges and dynamics faced by entrepreneurship and innovation in the face of profound changes in the digital era. Research methods to investigate the Future of Entrepreneurship and Innovation in the Digital Age can be directed through a combination of qualitative and quantitative approaches. This holistic approach enables a thorough understanding of the unique challenges and dynamics emerging in the context of technological change. This research is expected to provide in-depth insights into the dynamics of entrepreneurship and innovation in the digital age, helping entrepreneurs and stakeholders to understand changes and adjust their strategies.